Pengaruh Kualitas Pelayanan, Harga, Dan Kepercayaan Terhadap Kepuasan Pelanggan Jasa Ekspedisi J&T Express - Ekafianti, Firdayani; Sunaryo, Hadi; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research investigates the relationship between service quality, price, trust, and customer satisfaction in the context of J&T Express delivery services. Using a quantitative methodology with an associative framework, we surveyed 75 respondents via purposive sampling. The results of multiple linear regression analysis indicate that service quality, price, and trust simultaneously exert a significant impact on customer satisfaction. Moreover, each of these variables has a positive and significant individual effect on customer satisfaction. The study's findings offer actionable implications for the company to improve its service delivery and build trust with customers. Keywords: Service Quality, Price, Customer Trust, Customer Satisfaction